MEL-18 ACTS AS A TUMOR SUPPRESSOR BY REPRESSING BMI-1 EXPRESSION AND DOWN-REGULATING AKT ACTIVITY IN BREAST CANCER CELLS - Guo, Wei-Jian (2007)
The Bmi-1 oncogene is overexpressed in a number of malignancies including breast cancer. In addition to Bmi-1, mammalian cells also express four other polycomb group (PcG) proteins that are closely related to Bmi-1. Virtually nothing is known about the role of these PcG proteins in oncogenesis. We have recently reported that Mel-18, a Bmi-1–related PcG protein, negatively regulates Bmi-1 expression, and that its expression negatively correlates with Bmi-1 in proliferating and senescing human fibroblasts. Here, we report that the expression of Bmi-1 and Mel-18 inversely correlates in a number of breast cancer cell lines and in a significant number of breast tumor samples. Overexpression of Mel-18 results in repression of Bmi-1 and reduction of the transformed phenotype in malignant breast cancer cells. Furthermore, the repression of Bmi-1 by Mel-18 is accompanied by the reduction of Akt/protein kinase B (PKB) activity in breast cancer cells. Similarly, Bmi-1 knockdown using RNA interference approach results in down-regulation of Akt/PKB activity and reduction in transformed phenotype of MCF7 cells. Importantly, we show that overexpression of constitutively active Akt overrides tumor-suppressive effect of Mel-18 overexpression and the knockdown of Bmi-1 expression. Thus, our studies suggest that Mel-18 and Bmi-1 may regulate the Akt pathway in breast cancer cells, and that Mel-18 functions as a tumor suppressor by repressing the expression of Bmi-1 and consequently down-regulating Akt activity.